2019
DOI: 10.1097/ico.0000000000002242
|View full text |Cite
|
Sign up to set email alerts
|

Cost–Benefit and Cost–Utility Analysis of Amphotericin B Supplementation of Corneal Storage Media With Endothelial Keratoplasty-Prepared Tissue

Abstract: Purpose: To determine the cost-effectiveness of amphotericin B supplementation, we analyzed both current costs to treat postendothelial keratoplasty (EK) fungal infections and potential costs associated with amphotericin B supplementation. Methods: We collected 19 US cases of post-EK fungal eye infections from the published literature and assessed the associated costs from the literature. A survey of surgeons was also conducted with questions regarding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…It was concluded that amphotericin B supplementation is cost-effective and can prevent more than 69.62% of the post-EK fungal infections. [ 29 ] Based on this current experiment, the lowest concentration with a higher efficacy was observed with amphotericin B (0.5 μg/mL). Future research on endothelial toxicity (currently experiments are under process) with the above concentrations can guide us about the correct dosage and choice of the drug.…”
Section: Discussionmentioning
confidence: 76%
“…It was concluded that amphotericin B supplementation is cost-effective and can prevent more than 69.62% of the post-EK fungal infections. [ 29 ] Based on this current experiment, the lowest concentration with a higher efficacy was observed with amphotericin B (0.5 μg/mL). Future research on endothelial toxicity (currently experiments are under process) with the above concentrations can guide us about the correct dosage and choice of the drug.…”
Section: Discussionmentioning
confidence: 76%
“…Therefore, a review of post-EK keratitis/endophthalmitis found supplementation of amphotericin B to be effective in the corneal storage solution at a $100,000 qualityadjusted life-year level and if the intervention can prevent 70% of post-EK fungal infections. 68 Two commentaries were recently published advocating the pros 69 and cons 70 of supplementing corneal storage solutions with antifungals. After an increase in popularity of EK, fungal endophthalmitis post-EK 35 2000…”
Section: Antifungal Coverage and Cost-effectiveness In Hypothermic Co...mentioning
confidence: 99%
“…[38][39][40][41] Gibbons et al and Chiang et al evaluated the cost-effectiveness of antifungal supplementation and found that amphotericin B supplementation could be cost-effective in reducing the risk of fungal infections with endothelial grafts. 42,43 However, the hypothermic conditions may affect the pharmacokinetics of amphotericin. 16 A recent publication evaluated the effects of adding 0.255 ug/ml amphotericin to Optisol solution (Bausch & Lomb Inc, Bridgewater, NJ).…”
Section: Preventionmentioning
confidence: 99%